Studi Efisiensi Pompa Air Laut Energi Gelombang Tipe Flap - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
There are many sources of energy in nature such as solar. radiation, petroleum, coals, wind, tides and waves. The use of energy resources must consider its availability, influence on the environment, efficiency, and cost of operation. Sea waves provide a large amount of energy, but its recovery is limited. A water pump technology making use of wave energy comprising a flap, a piston and valve sistem can be used to increase sea water potential energy for various use. This research was done using physical model tests with various pipe piston, water depth, wave .period and head. The discharge obtained was measured three times for each combination. The model used a scale of approxiamately 1:20, based on the availability of facilities. Pump efficiency was measured by comparing output power with the input wave power. Results of the research indicate that the for first model (diameter of 11 cm), maximum pump efficiency was 7.87 %, it provide discharge of 0.0294 L/s at head of 35 cm, wave height of 3.35 cm and wave period of 1.79 second. The second model (diameter of 7 cm), produced maximum pump efficiency at 11.05 %, the maximum discharge 0.0393 lt/ s at total head of 30 cm, wave height of 6.63 cm, and wave period of 2.68 second.